Cell-Type Specific Changes in Glial Morphology and Glucocorticoid Expression During Stress and Aging in the Medial Prefrontal Cortex - Chan, Thomas E.; Grossman, Yael S.; Bloss, Erik B.; Janssen, William G.; Lou, Wendy; McEwen, Bruce S.; Dumitriu, Dani; Morrison, John H. (Frontiers in Aging Neuroscience, 2018)
Repeated exposure to stressors is known to produce large-scale remodeling of neurons within the prefrontal cortex. Recent work suggests stress-related forms of structural plasticity can interact with aging to drive distinct patterns of pyramidal cell morphological changes. However, little is known about how other cellular components within prefrontal cortex might be affected by these challenges. Here, we examined the effects of stress exposure and aging on medial prefrontal cortical glial subpopulations. Interestingly, we found no changes in glial morphology with stress exposure but a profound morphological change with aging. Furthermore, we found an upregulation of non-nuclear glucocorticoid receptors with aging, while nuclear levels remained largely unaffected. Both changes are selective for microglia, with no stress or aging effect found in astrocytes. Lastly, we show that the changes found within microglia inversely correlated with the density of dendritic spines on layer III pyramidal cells. These findings suggest microglia play a selective role in synaptic health within the aging brain.